SuperCollider in concert performance - Koutsomichalis, Marinos (My University, 2026)
A networked improvised music performance by Marinos Koutsomichalis, Scott Wilson, Carl Testa, Marcin Piotr Paczkowski. CODEFEST, co-organised by University of Turin and codexpo.